Teacher perceptions of a new performance evaluation system and their influence on practice: A within- and between-school level analysis - Matthew Finster; Anthony Milanowski (Arizona State University, 2018)
Teacher performance evaluation systems (PESs) are central to policy efforts to increase teacher effectiveness and student learning. We argue that for these reforms to work, PESs need to be treated as coherent systems, in which teachers perceive that there are linkages between the PES components. Using teacher survey data from a large, midwestern school district, this article explores the linkages between teacher perceptions of a new PES using confirmatory factor analysis (CFA), structural equation modeling (SEM), and multilevel CFA. We also examine whether a strong evaluation climate developed in this district. The CFA and SEM analysis demonstrate that teacher perceptions of PES are interrelated and linked to perceptions of changes in teaching practices and to the potential impact on student learning. The multilevel CFA demonstrates cross-level noninvariance, with fewer factors being identified at the school levels. These results suggest a need for a school‐level theory of action with corresponding school‐level constructs. While we did not find evidence of a shared strong evaluation climate, the results of the analysis illustrate the importance of examining within-school agreement, both to assess the reliability of between-school differences in average teacher perceptions and to assess whether schools are developing a strong evaluation climate.